ANALISIS KEMAMPUAN AEROBIK DAN ANAEROBIK TIM FUTSAL JOMBLO FC PONOROGO - MUCHLIS JUBAIRI, SURYA; WIDYAH KUSNANIK, NINING (Jurnal Prestasi Olahraga, 2020)
ABSTRACT AEROBIC AND ANAEROBIC ABILITY ANALYSIS OF FUTSAL TEAM JOMBLO FC PONOROGO TEAM Name : Surya Muchlis jubairi NIM : 14060474037 Study Program : S1 Sports Coaching Education Department : Sports Coaching Education Faculty : Faculty of Sports Science Name of Institute : Surabaya State University Lecturer : Dr. Nining Widyah Kusnanik S.Pd, M.Appl, Sc Year : 2018 Aerobic is the process of meeting energy needs that takes advantage of oxygen and has a long duration, whereas anaerobic is the fulfillment of the energy needs that take advantage of glycogen without any oxygen in it and have a very short duration. In this case, the research objective is determined the aerobic and anaerobic abilities of the Jomblo FC futsal team. This research is a quantitative descriptive study. To find out the aerobic and anaerobic abilities using test instruments, namely MFT, sprint, vertical jump, and shuttle run. The sample of this study is the whole existing in the population that makes this study a population research. The results of the study showed that aerobic ability is very low seen from the percentage of 2 athletes the percentage of 13.3% moderate category, 10 athletes percentage 66.6% less category, and 3 athletes the percentage of 20% is very poor category. The anaerobic ability of sprint tests is 1 athlete percentage 6.7% good category, 10 athletes percentage 66.7% moderate category, and 4 athletes percentage 26.7% less category. Shuttle Run is 2 athletes percentage 13.3% excellent category, 11 athletes percentage 73.4% good category, and 2 athletes percentage 13.3% moderate category. Vertical Jump is 2 athletes percentage 13.3% category very good, 4 athletes percentage 26.7% category good, 6 athletes percentage 40% category enough, 2 athletes percentage 13.3% category moderate, and 1 athlete percentage 6.7% category less. The conclusions of research into aerobic and anaerobic ability of the Jomblo fc Ponorogo futsal teams are aerobic ability using multistage fitness test items (MFT) get the results of a